Effectiveness of Organic Materials as Media in Sulfate Reducing Bacteria Inoculum to Changes on Acid Sulfate Soils - Mazlina, Mazlina; S Hanafiah, Asmarlaili; Rauf, A; Sigit Sutarta, Edy (International Journal of Engineering, Science and Information Technology, 2022)
Acid sulphate soils (ASS) had low pH, low nutrients availability and also soluble aluminium and iron were high. Inoculum of sulphate reducing bacteria (SRB) which organic matter as media could increased the soil pH, nutrient content and decrease sulfur-total of acid sulfate soils. The research was conducted in a randomized block design with two replications. This study used a randomized block design with two factors and two replications. The first factor was compost inoculum (C) was taken ten treatments from without anyÂ  inoculum SRB and 9 treatment with different types and dosages of organic matter as media. The second factor was the water content condition (K) namely of K1: 100% field capacity and K2: 110% field capacity. Different types and dosages of organic matter appear to influence the changes in soil properties (tends to decrease soil sulfate and increase soil pH, and nutrient content levels in soil and plant). Inoculum SRB of palm oil empty bunches and weed gave a higher sulfate reduction compared to C0 (without inoculums) or inoculums with carrier media that used rice straw in water content 100% or 110% field capacity (FC).